Electromagnetic Acceleration Device With More Stages - Kovařík, Martin (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
This paper describes the design and realization of multistage electromagnetic accelerating device (gun) and possibilities to increase its effectivity. Including a simulation of a magnetic circuit and designs of each components. Whole desing is focused on propper countermeasures against the damage of switching transistors.
Keywords: IGBT; multistage; coilgun